Research on online safety early warning technology for oil system of phase modifier. (July 2020) - Shuai, Yunfeng; Wu, Yanyan; Zhang, Enxian; Yu, Guoqiang; Yu, Dahai; Shen, Yongjun
Abstract: Lubricating oil is the blood of the machine, and health monitoring based on the quality of lubricating oil is an important means of condition based maintenance. The lubricating oil system is an important auxiliary system of the phase modifier. Metamorphic of the lubricating oil and contaminants carried by the lubricating oil will block the oil filter, scratch the seals and block or wear the components, which would cause the failure of the equipment. Particles and leakage generated when the equipment fails will also fall into the lubricating oil. Therefore, we can detect the indicators and pollutant content of the lubricating oil to speculate the equipment condition and make failure prediction. In view of the lack of operation and maintenance experience of rotating equipment in converter station staff, in order to ensure the safe and reliable operation of the converter station, this paper focuses on the research of online safety early warning technology, so as to improve the real-time and accuracy of lubricating oil diagnosis, reduce the probability of equipment failure, and improve enterprise benefits.